Analısıs Kebutuhan Pengembangan E-Lkpd Berbasıs Hots Berbantuan Lıveworksheet Untuk Peserta Dıdık Sekolah Dasar - Aliyah Hasanah; Suratmi; Laihat (Elementary Teacher Education Program, Majalengka University, 2023)
ABSTRACTThe development of the times and technology has an impact on every field, especially the field of education. 21st century skills require teachers to facilitate students in training the 4Cs including critical thinking, creativity, communication and collaboration. In learning, 21st century skills, especially critical thinking, can be integrated with the concept of HOTS (Higher Order Thingking Skill). To train students' skills in thinking in HOTS, fun and technology-assisted, of course, something is needed to support the learning process in the form of developing electronic student worksheets (E-LKPD). This study aims to analyze students' needs for Liveworksheet-Assisted HOTS-Based E-LKPD at SD Negeri 002 Palembang. This research uses research and development (R&D) methods with the ADDIE model. This study only discusses the first stage of the ADDIE model i.e. the analysis stage. The data collection technique used in this study is in the form of a literature study by collecting data by looking for relevant sources and a field study in the form of interviews with grade IV teachers of SD Negeri 002 Palembang. The results showed that the development of E-LKPD is needed that is able to facilitate students' critical thinking process, namely by developing Liveworksheet-Assisted HOTS Based E-LKPD to train students' critical thinking skills.